Parallel Offset Crack Interactions in Rock under Unloading Conditions - Zihan Zhou; Zhonghui Chen (Advances in Materials Science and Engineering)
Rock slopes contain numerous nonpenetrating intermittent joints which maintain stability under excavation disturbance. The tip interaction coefficient (IC) of parallel offset double cracks in a typical rock mass under unloading conditions was calculated in this study based on the superposition principle and fracture mechanics to determine the meso-influence law of intermittent joint interaction in the slope under the action of excavation. The influence of many factors on the said interaction was also analyzed theoretically. Lateral unloading tests were conducted on rock-like specimens with parallel offset cracks in addition to RFPA2D numerical simulation and theoretical analysis. The results show that a smaller length of rock bridge or staggered distance between the cracks results in more severe and sensitive interactions at the crack tip. The Type I interaction strength of the tip of the crack is not affected by the inclination angle of the crack, but shear failure gradually weakens as the angle changes. The shear failure of the tip of the crack is more sensitive to changes in the inclination angle when the cracks are closer to each other; the change is the most intense when α is about 60°. Lateral unloading test and RFPA2D numerical simulation results are in close agreement with the theoretical analysis, which validates the theoretical results. The current study shows the interaction of the parallel offset cracks in rock under unloading conditions and is conducive to the study of the meso-failure mechanism of the jointed rock slope in an open-pit mine under the action of excavation.